Efektifitas Teknik Relaksasi Otot Progresif Terhadap Kecemasan Pada Ibu Hamil Trimester I di UPTD. Puskesmas Kuta II - Ni Wayan Yoni Purwati (STIKES ADVAITA MEDIKA TABANAN, 2023)
Abstract Intoduction: Pregnancy is a physiological state in which various changes are experienced by the mother, both physical and psychological changes. Changes in conditions experienced by the mother during pregnancy can cause psychological discomfort in the form of anxiety. Progressive muscle relaxation therapy is a non-pharmacological method that can provide a feeling of relaxation to patients so as to reduce anxiety. The purpose of this study was to determine the effectiveness of progressive muscle relaxation techniques on anxiety in the first trimester of pregnant women. Metohds: This study used a quasi-experimental research design with a one group pre-post test design with purposive sampling, which involved 30 pregnant women. Anxiety was measured using the Anxiety Questionnaire related to pregnancy-revision 2 (PRAQ-R2) and then analyzed the data with the Wilcoxon t-test because the data were not normally distributed.Suggestion: The results showed a decrease in anxiety levels after being given an intervention where most of them experienced mild anxiety as many as 19 respondents (63.3%), not anxious as many as 9 respondents (30%) and only 2 respondents (3.3%) experienced moderate anxiety. Analysis with Wilcoxon obtained a p value = 0.000 where <0.05, so it means that there is a significant effect of progressive muscle relaxation techniques on the anxiety level of first trimester pregnant women at the Kuta II Health Center. It is hoped progressive muscle relaxation techniques can be used as material for consideration in providing comprehensive midwifery care pregnant women to reduce anxiety.